PENGARUH MODEL PEMBELAJARAN CHILDREN LEARNING IN SCIENCE (CLIS) TERHADAP HASIL BELAJAR IPA SISWA KELAS IV - Aisyah, Putri; Safrihady, Safrihady; Kamaruddin, Kamaruddin (JURNAL PENDIDIKAN DASAR, 2025)
Abstract: The purpose of this study was to state whether or not there was a difference in science learning outcomes of students using the Children Learning In Scince (CLIS) Learning Model with students who used the direct learning model for grade IV. The subjects in this study consisted of two classes, namely class IV A with 20 students and class IVB with 20 students. There were three instruments used in this study, namely test sheets, observation sheets, and documentation. This type of research is Quasi Experimental, where class IV B as an experiment that will be given treatment and class IV A as a control class that is not given treatment. The data analysis technique used a two-sample t-test, effect size, and percentage. Research results; 1) There is a difference in the science learning outcomes of students who use the Children Learning In Science (CLIS) Learning Model with students who are taught with a direct learning model, the calculation results show t_count = 5.559 and t_table = 1.686; 2) The Children Learning In Science (CLIS) Learning Model has a large influence on the science learning outcomes of grade IV students of SDN 85 Singkawang, with the calculation results of the effect size of 1.49; 3) The implementation of the Children Learning In Science (CLIS) Learning Model is in the very good category for science learning outcomes, with the calculation results of 92.66%. So from the results of the research that has been done, it can be concluded that "There is an Effect of the Children Learning In Science (CLIS) learning model on the science learning outcomes of grade V students of SDN 85 Singkawang”.Keywords: CLIS, Learning Outcomes, and ScienceAbstrak: Tujuan dari penelitian ini untuk menyatakan ada tidaknya pengaruh hasil belajar IPA siswa menggunakan Model Pembelajaran Children Learning In Science (CLIS) dengan siswa yang mengunakan model pembelajaran langsung kelas IV. Subjek dalam penelitian ini terdiri dari dua kelas yaitu kelas IV A yang berjumlah 20 Siswa dan kelas IVB yang berjumlah 20 siswa. Instrumen yang digunakan dalam penelitian ini ada tiga yaitu lembar tes, lembar observasi, dan dokumentasi. Jenis penelitian ini adalah Quasi Experimental, dimana kelas IV B sebagai eksperimen yang akan diberikan perlakuan dan kelas IV A sebagai kelas kontrol yang tidak diberi perlakuan. Teknik analisis data menggunakan uji t dua sampel, effect size, dan persentase. Hasil penelitian; 1) Terdapat perbedaan hasil belajar IPA siswa  yang menggunakan Model Pembelajaran Children Learning In Science (CLIS) dengan siswa yang  diajarkan dengan Model Pembelajaran Langsung, hasil perhitungan  menunjukkan  t_hitung = 5,559 dan t_tabel = 1,686; 2) Model Pembelajaran Children Learning In Science (CLIS) berpengaruh terhadap hasil belajar IPA siswa kelas IV SDN 85 Singkawang, dengan hasil perhitungan effect size sebesar 1,49; 3) Keterlaksanaan Model Pembelajaran Children Learning In Science (CLIS) dengan kategori sangat baik terhadap hasil belajar IPA, dengan hasil perhitungan 92,66%. Jadi dari hasil penelitian yang telah dilakukan dapat disimpulkan bahwa “Terdapat pengaruh model pembelajaran Children Learning In Science (CLIS) terhadap hasil belajar IPA siswa kelas V SDN 85 Singkawang”Kata Kunci: CLIS, Hasil Belajar, dan IPA